Quantifying the Vaccine-Induced Humoral Immune Response to Spike-Receptor Binding Domain as a Surrogate for Neutralization Testing Following mRNA-1273 (Spikevax) Vaccination Against COVID-19 - Kirste, Imke; Hortsch, Sayuri; Grunert, Veit Peter; Legault, Holly; Maglinao, Maha; Eichenlaub, Udo; Kashlan, Basel; Pajon, Rolando; Jochum, Simon (Infectious diseases and therapy, 2023)
Introduction There is a need for automated, high-throughput assays to quantify immune response after SARS-CoV-2 vaccination. This study assessed the combined utility of the Elecsys ® Anti-SARS-CoV-2 S (ACOV2S) and the Elecsys Anti-SARS-CoV-2 (ACOV2N) assays using samples from the mRNA-1273 (Spikevax™) phase 2 trial (NCT04405076). Methods Samples from 593 healthy participants in two age cohorts (18–54 and ≥ 55 years), who received two injections with placebo ( n = 198) or mRNA-1273 (50 μg [ n = 197] or 100 μg [ n = 198]), were collected at days 1 (first vaccination), 15, 29 (second vaccination), 43, and 57. ACOV2S results were used to assess humoral response to vaccination in different subgroups and were compared to live virus microneutralization assay. Samples from patients with either previous or concomitant infection (identified per ACOV2N) were analyzed separately. Results Receptor-binding domain-specific antibodies were readily detectable by ACOV2S for the vast majority of participants (174/189, 92.1% [50 μg dose] and 178/192, 92.7% [100 μg dose]) at the first post-vaccination assessment, with non-converters predominantly older in age. Seroconversion for all participants was observed at day 29 (before the second vaccine dose). Two weeks after the first dose, geometric mean concentration (GMC) of antibody levels was 1.37-fold higher in the 100 versus 50 μg group ( p = 0.0098), reducing to 1.09-fold 2 weeks after the second dose ( p = 0.0539, n.s.). In both dose groups, a more pronounced response was observed in the younger versus older age group on day 15 (50 μg, 2.49-fold [ p < 0.0001]; 100 μg, 3.94-fold [ p < 0.0001] higher GMC, respectively), and day 29 (1.93-fold, p = 0.0002, and 2.44-fold, p < 0.0001). Eight subjects had previous or concomitant SARS-CoV-2 infection; vaccination boosted their humoral response to very high ACOV2S results compared to infection-naïve recipients. ACOV2S strongly correlated with microneutralization (Pearson’s r = 0.779; p < 0.0001), including good qualitative agreement. Conclusion These results confirmed that ACOV2S is a highly valuable assay for tracking vaccine-related immune responses. Combined application with ACOV2N enables monitoring for breakthrough infection or stratification of previous natively infected individuals. The adaptive measuring range and high resolution of ACOV2S allow for early identification of seroconversion and resolution of very high titers and longitudinal differences between subgroups. Additionally, good correlation with live virus microneutralization suggests that ACOV2S is a reliable estimate of neutralization capacity in routine diagnostic settings.